PERSEPSI WAITER/ESS TERHADAP PERAN SUPERVISOR RESTAURANT DI THE AXANA HOTEL KOTA PADANG - Vioman, Raka Maulana; Kasmita, Kasmita; Pramudia, Heru (Journal of Home Economics and Tourism, 2017)
This research aims at how a leader action like supervisor for a few job description which is focused to controlling and guidance. After the researcher doing a observation in The Axana Hotel, Padang City, there is a some problem about controlling and guidance. Research purposes is for observe, knowing and describing for restaurant supervisor job description. This type of research is a descriptive qualitative research type. This research was conducted at The Axana Hotel, Padang City with adresses Bundo Kandung Street No. 14-16, Padang City. This research result concluded that in general the role of a supervisor in the food and beverage service department, especially in the restaurant has been in good category to provide supervision of the waiter / ess and for guidance in the category is quite good.Â Keywords: Perception, Supervisor Act, Controlling, Guidance